Pd‐Catalyzed Selective Remote Ring Opening of Polysubstituted Cyclopropanols. Issue 34 (22nd May 2018) - Singh, Sukhdev; Simaan, Marwan; Marek, Ilan
Abstract: The distant functionalization of ω‐ene cyclopropanols is induced by a Pd‐catalyzed Heck reaction triggering a "metal‐walk" and selective ring‐opening of the three‐membered ring. This approach provides a new class of acyclic aldehydes possessing concomitantly a stereodefined double bond and a quaternary carbon stereocenter α to the carbonyl group. Abstract : The distant functionalization of ω‐ene cyclopropanols, induced by a Pd‐catalyzed Heck reaction, triggered a "metal‐walk" and selective ring‐opening of the three‐membered ring. This approach provides a new class of acyclic aldehydes possessing concomitantly a stereodefined double bond and a quaternary carbon stereocenter at the α of the carbonyl group.